CD40L-stimulated B cells for ex-vivo expansion of polyspecific non-human primate regulatory T cells for translational studies. (28th December 2020) - Alonso-Guallart, P; Llore, N; Lopes, E; Kofman, S-B; Ho, S-H; Stern, J; Pierre, G; Bruestle, K; Tang, Q; Sykes, M; Griesemer, A
Summary: The therapeutic applications of regulatory T cells (Tregs ) include treating autoimmune diseases, graft- versus -host disease and induction of transplantation tolerance. For ex-vivo expanded Tregs to be used in deceased donor transplantation, they must be able to suppress T cell responses to a broad range of human leukocyte antigen (HLA). Here, we present a novel approach for the expansion of polyspecific Tregs in cynomolgus macaques that was adapted from a good manufacturing practice-compliant protocol. Tregs were isolated by fluorescence-activated cell sorting (FACS) and expanded in the presence of a panel of CD40L-stimulated B cells (CD40L-sBc). Prior to Treg culture, CD40L-sBc were expanded in vitro from multiple major histocompatibility complex (MHC)-disparate macaques. Expanded Tregs expressed high levels of forkhead box protein 3 (FoxP3) and Helios, a high percentage of Treg -specific demethylated region (TSDR) demethylation and strong suppression of naïve T cell responses in vitro . In addition, these Tregs produced low levels of inflammatory cytokines and were able to expand post-cryopreservation. Specificity assays confirmed that these Tregs were suppressive upon activation by any antigen-presenting cells (APCs) whose MHC was shared by CD40L-sBc used during expansion, proving that they are polyspecific. We developed an approach for the expansion of highly suppressive cynomolgus macaque polyspecific Tregs through the use of a combination of CD40L-engineered B cells with the potential to be translated to clinical studies. To our knowledge, this is the first report that uses a pool of MHC-mismatched CD40L-sBc to create polyspecific Tregs suitable for use in deceased-donor transplants. Graphical Abstract: